2017
DOI: 10.2147/ijwh.s115454
|View full text |Cite
|
Sign up to set email alerts
|

Implementing visual cervical cancer screening in Senegal: a cross-sectional study of risk factors and prevalence highlighting service utilization barriers

Abstract: BackgroundSenegal ranks 15th in the world in incidence of cervical cancer, the number one cause of cancer mortality among women in this country. The estimated participation rate for cervical cancer screening throughout Senegal is very low (6.9% of women 18–69 years old), especially in rural areas and among older age groups (only 1.9% of women above the age of 40 years). There are no reliable estimates of the prevalence of cervical dysplasia or risk factors for cervical dysplasia specific to rural Senegal. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Studies revealed an incidence rate of precancerous lesions that ranged from 5.7% to 28% in Senegal, which is comparable to a 10.1% incidence rate in similar low-income countries [40]. A cohort of Senegalese women revealed that the incidence of cervical cancer peaked between the ages of 45 and 54 years of age.…”
Section: Senegalmentioning
confidence: 83%
“…Studies revealed an incidence rate of precancerous lesions that ranged from 5.7% to 28% in Senegal, which is comparable to a 10.1% incidence rate in similar low-income countries [40]. A cohort of Senegalese women revealed that the incidence of cervical cancer peaked between the ages of 45 and 54 years of age.…”
Section: Senegalmentioning
confidence: 83%
“…The Sénégal-Peace Corps-UIC partnership has conducted implementation research on capacity building and quality improvement activities to achieve partnership, community, and research objectives that include informing priorities, improving health outcomes, and building knowledge. 19,20 In 2014, the partnership began to study the impact of a QI program on the supply-side (health service-level) determinants of cervical cancer screening and the implementation of regional health programmatic strategy.…”
Section: Global Disparities In Cervical Cancer Prevention and Controlmentioning
confidence: 99%
“…Furthermore, although women ages 40 + are at highest risk of cervical cancer, they are the least likely to seek cervical cancer screening services. 19 An important aim for this participatory QI approach is to improve health equity through a heightened community voice.…”
Section: Demand-side Barriersmentioning
confidence: 99%
“…Only 509, or 5% of eligible women targeted through a mass campaign that year, were screened and only 10% were 45 years or older. 16 The highest risk women, therefore, were the ones least likely to seek screening services. Despite a robust educational campaign that focused only on cervical cancer and screening service-related knowledge, screening rates through this focused effort were suboptimal.…”
Section: Cervical Cancer Screening Program Implementationmentioning
confidence: 99%
“…Given that a prior study in this region indicated that older women are less likely to seek cervical cancer screening, this is a notable knowledge gap. 16 Increased cervical cancer education is needed, including strategies and messages targeted to each gender.…”
Section: Risk Factors and Knowledgementioning
confidence: 99%